Current Research on Theory and Practice of Digital Libraries: Best Papers from TPDL 2019 & 2020 - Trond Aalberg; Fabien Duchateau; Mark Hall; Tanja Mercun; Thomas Risse (International Journal on Digital Libraries, 2022)
This volume presents a special issue on selected papers from the 2019 & 2020 editions of the International Conference on Theory and Practice of Digital Libraries (TPDL). They cover different research areas within Digital Libraries, from Ontology and Linked Data to quality in Web Archives and Topic Detection. We first provide a brief overview of both TPDL editions, and we introduce the selected papers.
Keywords: 000; Digital libraries; TPDL conference; Special issue